The Factors Affecting to Government’s Expenditure of Lao PDR - SENGPHETPHAIVAN, somsay; SOMSAMONE, Vilayphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This paper aims to analyze the factors affecting the government’s expenditure of Lao PDR. Using the time series data from 2000-2022 which retried from the bank of Lao PDR and implied with the ARDL model. The empirical results found that there is a long-term relationship and ARDL (2, 2, 1, 2, 2) model were used. The empirical results found that in the long run, the tax revenue and economic growth have a positive relationship with the government’s expenditure with a statistical significance level of 0.01 and 0.1 respectively. While inflation and money supply are not statistically significant. In the short term, tax revenue, economic growth rate and money supply affect the government’s expenditure with statistically significant effect, while the inflation rate does not have a statistically significant. Tax revenue and economic growth rate affect the government’s expenditure in the opposite direction with a significance level of 0.05 and contrary to the hypothesis. The money supply affects the government’s expenditure in the same direction with a statistically significant level of 0.05 and according to the hypothesis. Which the coefficient of the spread adjustment to the long run equilibrium is equal to 90.97%.